Making good schools linking school effectiveness and school improvement (Educational management series, 1996)
The disciplines of school effectiveness research and school improvement practice and research have been apart for too long. This book is the first major attempt by leading writers and practitioners in these fields to bring the areas together in a coherent way. Existing knowledge about the characteristics of 'good' schools is outlined, together with the knowledge base about how to 'make schools good schools'. The book also makes an entirely original contribution to re-thinking practice in school improvement that can revolutionise our thinking in the late 1990s and which can be of use to academics, policy-makers and practitioners.